Quantitative tracking of inflammatory activity at the peak and trough plasma levels of tofacitinib, a Janus kinase inhibitor, via in vivo 18F‐FDG PET. (29th October 2019) - Raychaudhuri, Sanchita; Abria, Christine; Harmany, Zachary T.; Smith, Charles M.; Kundu‐Raychaudhuri, Smriti; Raychaudhuri, Siba P.; Chaudhari, Abhijit J.
Abstract: Purpose: To assess the capability of in vivo positron emission tomography (PET) using 18 F‐fluorodeoxyglucose ( 18 F‐FDG) to quantify changes in inflammatory activity in response to tofacitinib, a Janus kinase (JAK) inhibitor, over a timeframe of a few hours to few days in a preclinical model of rheumatoid arthritis (RA). Methods: Twenty‐four mice with collagen‐induced arthritis in the following groups were assessed: Group 1, where the changes in PET measures for the extremity joints were evaluated at the peak and trough plasma drug levels after administration of a single dose of tofacitinib (4 hours apart); Group 2, where joint PET measures were assessed before treatment and after 6 days of administration of a daily dose of tofacitinib; and group 3 (controls), where joint PET measures were derived from the same mice, 6 days apart. Results: At about peak plasma levels of the drug after a single tofacitinib administration, there was a reduction in PET measures compared to pretreatment values, suggesting decreased inflammatory activity. These measures were equivalent to those obtained after 6 days of daily dosing by tofacitinib. However, PET measures at trough plasma levels of the drug from tofacitinib administration were significantly higher than those at peak plasma drug levels and equivalent to pretreatment measures. There were insignificant changes in PET measures for the control animals. Conclusion: 18 F‐FDG PET can detect changes in inflammatory activity occurring in response to the JAK inhibitor tofacitinib: (a) during peak and trough plasma drug levels, that is within mere hours of treatment; and (b) over a span of days.